FACTORS THAT CONTRIBUTE TOWARDS POOR PERFORMANCE OF STUDENTS IN SCIENCE IN RURAL SCHOOLS IN TSHOLOTSHO DISTRICT IN MATABELELAND PROVINCE IN ZIMBABWE - NDLOVU, FRANCIS (IJRDO- Journal of Educational Research, 2017)
This study sort to investigate learners’ attributions on high failure in science examinations in rural secondary schools in Tsholotsho district in Matabeleland North Province of Zimbabwe which has a student population of 2300 at Ordinary Level. A total of 400 respondents were used of which 240 were girls and 160 were boys. The research instrument used was the questionnaire which had both close ended and open ended questions. Descriptive statistical analysis was used to interpret data. The study revealed that pupils attributed their failure mainly to lack of material resources, poor teaching methods, bad teacher behaviour, and poor grounding in the subject at lower levels as well as their fear of the subject. The study recommends that the Ministry of Education should embark on serious in service training science teachers. Teachers should also embark on team teaching to assist each other on the subject. Finally, pupils should be motivated to view science like the rest of the subjects in the school curriculum.